On the Verge of Liminality: A Pipe Dream or an attained Eldorado in Laila Lalami’s Hope and Other Dangerous Pursuits. - Issafi, Hamid; Ouladhadda, Aziz (International Journal of Language and Literary Studies, 2025)
Laila Lalami’s novel Hope and Other Dangerous Pursuits (2008) presents a poignant exploration of migration and its associated motives and challenges, interwoven within the context of contemporary Morocco. The chief concern of this corpus-based, qualitative study is to analyse the central themes of the novel. Methodologically speaking, in analysing themes of this novel, the authors of this study utilise Postcolonial theory. Concepts such as liminality, hybridity, diaspora, orientalism and the politics of representation are used as tools of analysis. An understanding of the complexities of identity and belonging in a Postcolonial landscape can be attained through an examination of the characters’ journeys, both physical and emotional.